International Students and the Academic Library: A Case Study - Morrissey, Renée; Given, Lisa M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper presents a pilot study that examined the experiences of Chinese graduate students in using the University of Alberta Libraries. The findings outline the challenges faced by students with respect to working in a second language and navigating library technologies, with a focus on the students’ information literacy skills. Cet article présente une étude pilote qui a examiné les expériences des étudiants chinois de 3e cycle qui utilisent les bibliothèques universitaires de l’Université d’Alberta. Les résultats mettent en relief les défis auxquels les étudiants sont confrontés lors de l’utilisation d’une langue seconde et des technologies offertes par les bibliothèques, et s’attardent sur les compétences en culture de l’information des étudiants.